IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Lukman Ali Mustofa (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
Improving the quality of education is not a minor task because it not only deals with technical issues, but covers complex issues. Public expectations of quality education in line with the demands of the business world to obtain quality human resources. Thus education providers must be able to respond and accommodate these expectations and demands in the decision-making process for improving the quality of education. This confirms that in the decision-making process for improving the quality of education, various school-based management (SBM) theory, perspective and terms of reference can be used. This gives the consequence that schools should be a major part of the decision-making process in improving the quality of education. While the community is required for participation in order to better understand education, the educators and education personnel, as well as the community contribute greatly in terms of determining the quality of education.Key Word: implementation, MBS, education quality